Adaptive Encryption Strategies for ERP Data Exchange: Leveraging Machine Learning to Optimize Secure File Transfer Protocols - Manoj Varma Lakhamraju,Rishi Venkat, Shubham Metha, Nikhil Sagar Miriyala (South Eastern European Journal of Public Health, 2025)
The backbone of contemporary businesses, as it enables the integration and control of essential business processes, is Enterprise Resource Planning (ERP) systems. Particularly within Human Capital Management (HCM) modules managing extremely sensitive employee information, secure file transport is of utmost importance. Including payroll data, regulatory documents, and personally identifiable information (PII), these data transactions make privacy utmost concern. Though powerful in several settings, traditional encryption methods usually lack the flexibility needed to deal with the changing nature of modern corporate landscapes. Especially in conditions of changing threat levels and variable network connectivity, this inflexibility might result in poor equilibrium of system performance and security needs. The study presents an unconventional approach: using machine learning (ML) to develop adaptive encryption policies for ERP systems. ML-driven solutions can dynamically change encryption protocols depending on real-time evaluations of data sensitivity, network conditions, and developing threats, unlike static encryption techniques which work on fixed sets. These approaches guarantee that data security is not violated or too taxing for system performance by means of predictive analysis, anomaly finding, and performance optimization. The model this paper offers introduces several revolutionary approaches. First, it uses predictive analytics to predict possible threats and thus proactive changes to encryption protocols can take place. Second, it uses ML algorithms to sort data by sensitivity, therefore guaranteeing that very sensitive data is safeguarded with the strongest encryption possible. Thirdly, behavioral analytics are fused to spot anomalies in file transfer operations, activating improved security measures in case doubtful patterns show themselves. Taken together, these features represent a major advance in the way ERP systems could handle secure data exchanges. This paper is distinctive among others in its attention to HCM-specific activities in ERP systems. Although adaptive encryption has been debated more generally, this study customizes the technique to meet the difficulties HCM data presents. For example, employee records need to adhere with strict statutes including GDPR and CCPA, therefore compounding the sophistication of secure file transfer. The suggested architecture not only improves security by addressing these subtleties but also guarantees regulatory compliance and gives businesses a complete and strong solution. Adaptive encryption technologies come with their own set of difficulties in deployment. Along with sensible answers, we thoroughly go over issues such as user resistance, computational overhead, and compatibility with current ERP systems. For example, using cloud-based resources might help to lower computational demands; modular encrypting engines could guarantee smooth integration with several different ERP systems. Furthermore, user training programs can help to fight resistance by emphasizing the practical advantages of improved security. Equally important in this study is the balance it strikes between performance and security. Especially when handling great amounts of information, conventional encryption techniques usually have notable performance compromises. By contrast, the adaptive schemes suggested here fine-tune encryption intensity depending on current circumstances to avoid underperformance. For HCM modules especially, where data processing delays can interfere with other time-sensitive activities, this balance is quite vital. Future research in this field offers even more potential progress. Possible avenues of exploration are investigating quantum-resistant encryption methods, refining ML models to enhance predictive accuracy, and marrying blockchain technology for unalterable audit trails. Moreover, improving its applicability and value would be to broaden the adaptive encryption model to cover other ERP features including finance and supply chain management. Finally, this document provides a thorough and original strategy for protecting ERP data exchanges with special emphasis on HCM transactions. Combining the static and dynamic characteristics of machine learning helps to provide a strong response to the changing demands of data security. Beyond improving the level of safe file transmission in ERP systems, this study also lays the groundwork for further breakthroughs in this vital sector.